First Report of a Gall Midge Species (Diptera: Cecidomyiidae) Associated With Pistachios. (9th December 2020) - Sirjani, Farshid O; Lewis, Edwin E
Abstract: A new dipterous pest is reported, for the first time, on commercial pistachios from Sirjan, Kerman province, Iran. The genus of the insect was determined to be Resseliella Seitner (Diptera: Cecidomyiidae). Adults are light brown to brown in color and 0.8–1.5 mm in length with females, generally, slightly larger than males. Females have an elongated ovipositor, which is characteristic of the genus. Larvae are orange in color, 2–3 mm in length in the later instars, feed under bark without inducing galls, and cause branch dieback on trees of various ages. Brown to black discolorations are observed on plant tissues under bark where the larvae feed. Infestations observed on current and the previous—year's growths, ranged from 0.5 to 1.2 cm in diameter, and all located in outer branches. Dry leaves and fruit clusters on infested branches remain attached, which may be used to recognize infestation by the gall midge. Dark-colored, sunken spots with splits on the bark located at the base of the wilted sections of the shoots also are symptoms of Resseliella sp . larval activity. Species-level identification of the gall midge is currently underway.